Synthesis of Phenethyl-aza-ß-Lactam (1,2-Dimethyl4(R,S)-Phenethyl-[1,2]Diazetidin-3-One) - Ritmaleni Ritmaleni; Varinder K Anggarwal (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2005)
Racemic spiro-epoxide, (7RS, 1RS, 3RS)-phenethyl-10-oxa-1,3-dithiaspiro[6,7]octane 1,3-dioxide 12, can be synthesised in four step reactions, sequences starting from the commercially available 1,3-dithiane 8. The synthesis of aza ß-lactam, 1,2-dimethyl-4(R,S)-phenethyl-[1,2]diazetidin-3one 13, was successfully carried out by opening the epoxide by 1,2-dimethyl hydrazine salt in moderate yield. Keywords : epoxide, aza-ß-lactam